Analisis Framing Film Vina: Sebelum 7 Hari dalam Media Sosial Tiktok dan X - Adinda Dwi Mulyani; Arfian Suryasuciramdhan; Ine Fitrianingsih; Muadz Alfayeed (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
The tragedy of Vina Cirebon, a 16 year old girl who was brutally murdered by eleven people in 2016. The media actually used framing to present the case, which led to the creation of a film entitled "Vina: Sebelum 7 Hari." This film attempts to raise awareness about violence and sexual exploitation, as well as to reopen the case, and look for three identified criminals. Anggy Umbara defended the depiction of the subject in the film. However, the film received criticism for its depiction of the subject, leading to a lack of moral support and a reversal of the issue. This research uses qualitative research methods, such as Robert N Entman's framing analysis, to investigate this problem. This research aims to explore the media portrayal of this case and its impact on public perceptions of this issue. This research also aims to understand the role of the media in shaping public perceptions of this issue.